Capital Structure, Asset Turnover, and Service Quality among IDX-Listed Private Hospital Groups: Evidence from Panel Data Analysis - Rafika Aini (CV. Get Press Indonesia, 2026)
This study examines the association between capital structure and asset utilization with service quality among IDX-listed private hospital groups in Indonesia. The study employs an observational quantitative design using panel data rather than a causal-comparative approach. The sample consists of seven hospital groups observed over the 2021–2024 period, resulting in 28 firm-year observations. Financial data were obtained from audited annual reports, while service quality is measured using the Patient Satisfaction Index (PSI) reported in sustainability reports. National Quality Indicators (NQI) are used only as contextual references and are not included in the regression model. The empirical model applies panel data regression to estimate the relationship between Debt to Equity Ratio (DER), Total Asset Turnover (TATO), and PSI. The findings indicate that DER is negatively associated with PSI, while TATO shows a positive association. These results should be interpreted as statistical associations rather than causal relationships. The study contributes by providing empirical evidence on how financial indicators relate to perceived service quality within the context of Indonesian private hospital groups.